Contribution of Tipu Sultan to rocket technology - Ameer Amsa, Mohamad Ghazali; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective of this chapter is to highlight the contribution of Sultan Fateh Ali Tipu (1750-1799 A.D), the Sultan ofMysore, who was the pioneer of iron-cased rocket artillery technology. Tipu ruled Mysore for 17 years (l782-1799).The history of rockets or 'fireerrors' invention started from 1232 by Chinese and then followed by Europeans in the 14th and 15th centuries. Rocket bodies in this period were built using light materials such as bamboo, wood or paper since these materials can be easily obtained. However, towards the beginning of 16th century, the military scientists put more concentration to the development of canon. Thus, rockets was neglected due to invention and large improvement of canon. In the 18th century, rocket application reemerged during the Mysore time under the rule of Hyder Ali, (Tipu's father) and Tipu with totally improved version which was more superior than canon and existing rockets in China and Europe. The reemergence of the rockets created significant history in Indo-British technology